USP35 regulates mitotic progression by modulating the stability of Aurora B - Park, Jinyoung; Kwon, Mi-Sun; Kim, Eunice EunKyeong; Lee, Hyunsook; Song, Eun Joo (Nature Publishing Group, 2018)
Although approximately 100 deubiquitinating enzymes (DUBs) are encoded in the human genome, very little is known about the DUBs that function in mitosis. Here, we demonstrate that DUB USP35 functions as a mitotic regulator by controlling the protein levels and downstream signaling of Aurora B and the depletion of USP35 eventually leads to several mitotic defects including cytokinesis failures. USP35 binds to and deubiquitinates Aurora B, and inhibits the APC(CDH1)-mediated proteasomal degradation of Aurora B, thus maintaining its steady-state levels during mitosis. In addition, the loss of USP35 decreases the phosphorylation of histone H3-Ser10, an Aurora B substrate. Finally, the transcription factor FoxM1 promotes the expression of USP35, as well as that of Aurora B, during the cell cycle. Our findings suggest that USP35 regulates the stability and function of Aurora B by blocking APC(CDH1)-induced proteasomal degradation, thereby controlling mitotic progression.